2007
DOI: 10.1088/0957-0233/18/2/s10
|View full text |Cite
|
Sign up to set email alerts
|

Calibration strategies for scanning probe metrology

Abstract: Within the Dutch standards laboratory (NMi Van Swinden Laboratorium) a traceable atomic force microscope (AFM) is currently being developed where we aim at a measurement uncertainty of 1 nm. As part of this development novel methods have been developed for the calibration of this instrument. The SPM has been constructed using a commercial AFM head that has been embedded in a metrology frame using an accurate 3D translation stage. The position of the AFM probe relative to the sample is determined along three or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…(10) and (11) and the fitting lines illustrate that the lateral error can be reduced effectively by the decrease of the misalignment (angle deviation).…”
Section: The Measurement Of the Linear Displacementmentioning
confidence: 98%
See 2 more Smart Citations
“…(10) and (11) and the fitting lines illustrate that the lateral error can be reduced effectively by the decrease of the misalignment (angle deviation).…”
Section: The Measurement Of the Linear Displacementmentioning
confidence: 98%
“…EX 2 = 0.0005y + 0.0278 (11) EX 1, EX 2 mean the lateral errors of X-measurement of misalignments under the state 1 and after 2 respectively; y means the displacement of the linear Y-motion, also means lateral displacement of X-mirror for X-measurement.…”
Section: The Measurement Of the Linear Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…1, which defines the coordinate system of the instrument. Experience in characterizing mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that the metrological frame is the dominant source of measurement uncertainties arising from alignment errors, particularly Abbé errors and nonorthogonality of the measurement axes, and environmental vibration. To achieve the target total uncertainty of dimensional measurements, minimizing these contributions is a principal consideration in the design of the metrological frame and the material selected for its construction.…”
Section: System Integrationmentioning
confidence: 99%
“…1,2 The challenge in realizing this mSPM concept is to create a macroscopic mechanical instrument capable of traceable dimensional measurement at the nanoscale with a combined uncertainty of less than 1 nm. Experience in designing ultraprecision mechanical stages and instruments 3 and in operating similar mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that there are many contributions to the uncertainty of the displacement measurements. These include alignment errors (particularly Abbé errors 10 ), deformations of the mechanical structures (for instance, due to thermal expansion), motion errors of the translation stage, form errors of the interferometer mirrors, nonlinearities of the interferometers, and fluctuations in the refractive index of air.…”
Section: Introductionmentioning
confidence: 99%